Solution of Polynomial Equations with Nested Radicals

Solution of Polynomial Equations with Nested Radicals

Solution of Polynomial Equations with Nested Radicals Nikos Bagis Stenimahou 5 Edessa Pellas 58200, Greece [email protected] Abstract In this article we present solutions of certain polynomial equations in periodic nested radicals. Keywords: Nested Radicals; Bring Radicals; Iterations; Quintic; Sextic; Equations; Polynomials; Solutions; Higher functions; 1 Introduction In (1758) Lambert considered the trinomial equation xm + q = x (1) and solve it giving x as a series of q. Euler, write the same equation into, the more consistent and symmetrical form xa xb = (a b)νxa+b, (2) − − using the transformation x x−b and setting m = ab, q = (a b)ν in (1). Euler gave his solution as → − 1 1 xn =1+ nν + n(n + a + b)µ2 + n(n + a +2b)(n +2a + b)+ 2 6 1 + n(n + a +3b)(n +2a +2b)(n +3a + b)ν4+ 24 arXiv:1406.1948v4 [math.GM] 17 Dec 2020 1 + n(n + a +4b)(n +2a +3b)(n +3a +2b)(n +4a + b)ν5 + ... (3) 120 The equation of Lambert and Euler can formulated in the next (see [4] pg.306- 307): Theorem 1. The equation aqxp + xq = 1 (4) 1 admits root x such that ∞ n Γ( n + pk /q)( qa)k xn = { } − , n =1, 2, 3,... (5) q Γ( n + pk /q k + 1)k! =0 Xk { } − where Γ(x) is Euler’s the Gamma function. d 1/d Moreover if someone defines √x := x , where d Q+ 0 , then the solution x of (4) can given in nested radicals: ∈ −{ } q q/p x = 1 aq 1 aq q/p 1 aq q/p√1 . .. (6) s − − − − r q Turn now into the general quintic equation ax5 + bx4 + cx3 + dx2 + ex + f =0. (7) This equation can reduced by means of a Tchirnhausen transform (see [1]) into x5 + Ax + B =0. (8) We can solve this last equation using the arguments of Lambert and Euler since it is of the form (4). This can be done defining the hypergeometric function 1 2 3 4 1 3 5 3125t4 BR(t)= t 4F3 , , , ; , , ; , (9) − · 5 5 5 5 2 4 4 − 256 then according to Theorem 1: Theorem 2. The solution of (8) is 4 55 5 4 A −A x = − BR B (10) q r 5 − 4 and for (8) also holds 5 5 5 x = B A B A B A√5 B ... (11) s− − − − − − − − r q 2 The sextic equation It is true that in nested radicals terminology we can do much more than that. Consider the following general type of equation ax2µ + bxµ + c = xν , (12) 2 then (12) can be written in the form 2 b ∆2 a xµ + = xν , (13) 2a − 4a where ∆ = √b2 4ac. Hence − 2 µ b ∆ 1 ν x = − + 2 + x 2a r4a a or 2 µ b ∆ 1 ν x = − + 2 + x . s 2a r4a a Hence 2 µ/ν ν b ∆ 1 ν x = − + 2 + x (14) s 2a r4a a From the above we get: Theorem 3. The solution of (12) is µ 2 µ/ν 2 2 v b ∆ 1 b ∆ 1 µ/ν b ∆ u v v x = u− + u 2 + − + v 2 + − + 2 + ... (15) u 2a u4a a u 2a u4a a s 2a 4a u u u u r u u u t t t t Corollary 1. The general sextic equation ax6 + bx5 + cx4 + dx3 + ex2 + fx + g = 0 (16) is always solvable with periodic nested radicals. Proof. We know (see [1]) that all sextic equations, of the most general form (16) are equivalent by means of a Tchirnhausen transform y = kx4 + lx3 + mx2 + nx + s (17) to the form 6 2 y + e1y + f1y + g1 = 0 (18) But the last equation is of the form (12) with µ = 1 and ν = 6 and have solution 2 1 6 2 2 v / 1 6 f1 u ∆1 1 v f1 ∆1 1 / f1 ∆1 y = − + u 2 u− + v 2 v− + 2 + ... (19) 2e1 u4e1 − e1 u 2e1 u4e1 − e1 u 2e1 s4e1 u u u u u u u t t t t 3 2 where ∆1 = f1 4e1g1. Hence knowing y we find x from (17) and get the solvability of (16) in− nested periodic radicals. More precisely it holds p kx4 + lx3 + mx2 + nx + s = 2 1 6 2 2 v / 1 6 f1 u ∆1 1 v f1 ∆1 1 / f1 ∆1 = − + u 2 u− + v 2 v− + 2 + ... (20) 2e1 u4e1 − e1 u 2e1 u4e1 − e1 u 2e1 s4e1 u u u u u u u t t t t Corollary 2. If Im(τ) > 0 and jτ denotes the j-invariant, then − 5/3 1 2πiτ 5 2πiτ 5 5/3 R e 11 R e = jτ − − 3/5 125 12500 3/5 125 12500 = v− + v + − + + . ., (21) u j u j2 v j j2 u τ u τ u τ s τ u u u u t t where R(q) is thet Rogers-Ramanujan continued fraction: q1/5 q q2 q3 R(q)= ... , q < 1 (22) 1+ 1+ 1+ 1+ | | Proof. 1/3 1/3 1/3 Equation (12) for a =1/jτ , b = 250/jτ , c = 3125/jτ and µ = 1, ν =5/3 takes the form 2 1/3 5/3 x + 250x +3125 = jr x , (23) which is a simplified form of Klein’s equation for the icosahedron (see [2] and [3]) and have solution x = Y = R(q2)−5 11 R(q2)5. From Theorem 3 we τ − − can express Yτ in nested-periodical radicals. This completes the proof. 2 2 b 5/3 Note. For more details about equation ax + bx + 20a = C1x one can see [2]. 3 A solution of a tetranomial polynomial Consider now the generalization of the Bring radical function as follows: Set p = ν and q = ν 1, x = X−1 in (4), then it becomes − − − a(ν 1)X ν + X ν+1 =1 − Multiply both sides with Xν and set a a/(ν 1), then → − Xν = X + a (24) 4 This last equation according to Theorem 1 have solution ∞ −1 1 Γ[(1 + νn)/(ν 1)] ( a)n X = − − , (25) ν 1 Γ[( 1+ νn)/(ν 1) n + 1] n! n=0 ! − X − − − which is a hypergeometric function that we call ν th order Bring radical. Also the power Xµ has expansion − ∞ −1 µ Γ[(µ + νn)/(ν 1)] ( a)n Xµ = − − . (26) ν 1 Γ[(µ + νn)/(ν 1) n + 1] n! n=0 ! − X − − A simple way to write (25),(26) is ∞ −1 νn+1 ( a)n X = BR (a)= ν−1 − (27) ν n νn +1 n=0 ! X and from Theorem 1: ∞ n µ ( 1) k1n + λ1 n X = λ1 − a , (28) k1n + λ1 n n=0 X ν −µ where k1 = ν−1 and λ1 = ν−1 . Hence we lead to the following Definition 1. We call ”General Bring Radical” the function ∞ n µ ( 1) k1n + λ1 n BRν,µ(a) := (BRν (a)) = λ1 − a , (29) k1n + λ1 n n=0 X ν −µ where k1 = ν−1 and λ1 = ν−1 . Assume now the following equation kXµ = Xν X l. (30) − − If Hν (u) is a function such that H (u)ν H (u) l = u, (31) ν − ν − then equation (30) have solution X2 = Hν (u0) such that ν µ H (u0) H (u0) l = u0 = kH (u0) . ν − ν − ν But H (u)= BR (l + u), u D, (32) ν ν ∀ ∈ 5 where D is a suitable domain. Hence X2 = Hν (u0)= BRν (l + u0)= = BRν (l + kBRν,µ (l + kBRν,µ(l + ...))) (33) and we get the following Theorem 4. The equation Xν = kXµ + X + l (34) admits solution X2 given by µ ξ = l + kBRν (ξ) , X2 = BRν (ξ) (35) Setting this into nested Bring radicals we have X2 = BRν (l + kBRν,µ (l + kBRν,µ(l + ...))) (36) Application. Assume the equation Xµ = X2 X 1. (37) − − Then µ R and ν = 2 and if ∈ 1+ √1+4x f0(x) := BR2 1(x)= (38) , 2 and µ 1+ √1+4x f(x) := BR2 (x)= (39) ,µ 2 the above equation (37) admits solution X2 = f0 (1 + f (1 + f(1 + ...))) . (40) Theorem 5. Assume the equation Xν = kXµ + X + l, (41) −1 ν −µ with ν>µ and k , l , kl < 1. Set k1 = , λ1 = , | | | | | | ν−1 ν−1 ∞ s k1s + λ1n n f(s; x) := xn (42) n s (s n + 1)(k1s + λ1n) n=1 X − and ∞ s −1 s g(w) := w + wλ1 ( 1) f s; kw w . (43) − s=0 X 6 Then a solution of (41) is X2 = BRν (g(l)) . (44) Proof. It is clear that if X2 is the desired root of the equation (41), then also X2 = BRν (ξ), where ξ = l + kBRν,µ (ξ). But according to Lagrange theorem (see [6] pg 133), we have ∞ kn dn−1 ξ = l + (BR (l))n (45) n! dln−1 ν,µ n=1 X n and (BRν,µ(x)) = BRν,µn(x). Using expansion (29) we arrive to a double sum we rearrange and get the result. Example. Assume that ν = 2, µ =1/2 and l =1/5, k =1/52, then X1/2 = 5 25X + 25X2 (46) − − and 1+ √1+4x BR2 1(x)= (47) , 2 The polynomial f s; kl−1 is 1 sC2s−1,s 1 s s 3 1 f s; = 3F2 1 s, , 1 ; , 2 2s; + 5 50s 25 · − 2 − 2 − 2 2 − 25 − 1 2C2s− 2 ,s 1 1 s s 1 3 1 + 3F2 s, , ; , 2s; (48) 20s 5 · 2 − 2 − 2 −2 2 2 − 25 − and g will be ∞ 1 1 − 1 g(l)= ( 1)s5 sf s; , (49) 5 − 10 − 5 s=0 X where we have denoted n C := .

View Full Text

Details

  • File Type
    pdf
  • Upload Time
    -
  • Content Languages
    English
  • Upload User
    Anonymous/Not logged-in
  • File Pages
    9 Page
  • File Size
    -

Download

Channel Download Status
Express Download Enable

Copyright

We respect the copyrights and intellectual property rights of all users. All uploaded documents are either original works of the uploader or authorized works of the rightful owners.

  • Not to be reproduced or distributed without explicit permission.
  • Not used for commercial purposes outside of approved use cases.
  • Not used to infringe on the rights of the original creators.
  • If you believe any content infringes your copyright, please contact us immediately.

Support

For help with questions, suggestions, or problems, please contact us